MUCORMYCOSIS IN HEMATOLOGIC PATIENTS: A REVIEW - García-Romero Maria Teresa; García-Méndez Jorge; Arenas Roberto (Our Dermatology Online, 2011)
Most invasive fungal infections occur in patients with hematologic malignancies and the prevalence has increased steadily in recent years due to intensive cytotoxic chemotherapies, stem cell transplantation, myeloablative radiation therapy, and the use of corticosteroids, cyclosporine or new immunosuppressive agents. Although Candida is the main fungal agent involved in invasive fungal infection (IFI), an increasing number of infections are caused by molds, mostly Aspergillus spp, but in the last 20 years other emerging fungal pathogens such as Zygomycetes causing mucormycosis have appeared with higher mortality rates. The rhinocerebral and pulmonary forms of mucormycosis together with disseminated disease have the highest mortality (78-100%). Zygomycetes characteristically invade blood vessels, causing thrombosis and infarction with necrosis and scarring. Rapid diagnosis of zygomycosis is vital for management and therapy since these infections progress rapidly. Treatment should combine early aggressive surgical excision of the necrotic lesions, restoration of immune function if possible, and amphotericin B at a dose of 1-1.5 mg/kg or a new antifungal such as posaconazole.